Analisa Penentuan Jenis Olahraga Untuk Anak Intelektual Disabilitas( ID) Dengan Menggunakan Fuzzy Inference Systemmetode Sugeno - Kusuma Hati - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2015)
Abstract - Intellectual Disability is another word from mental retardation or mental retardation or mental retardation that causes a decrease in overall intellectual function that significantly and directly led to disruption of social adaptation, and manifested during the developmental period. This study was conducted to analyze the determination of the type of exercise that is appropriate for children with intellectual disabilities (ID) whether olagraga bocce, may only be four categories of sports (gymnastics, athletics, swimming, football) or 7 categories of sports (gymnastics, athletics, swimming, football, basketball, badminton, table tennis) to see an assessment of the fine and gross motor motor skills of the child. It is expected to provide information and facilitate the public, especially parents who have children with intellectual disabilities by (ID) in order to better determine the right type of exercise and can be done to help the growth and motor development of children. The benefits of this research is to produce applications that can help determine the right type of exercise for children with intellectual disabilities (ID) that is carried out with the approach Sugeno Fuzzy Inference System Method with R2014a Matlab Toolbox. Determination of the type of exercise for children with Intellectual Disability (ID) using this method to get the Sugeno defuzzification = 34.33, which means that the average child ID has the ability to follow the 4 types of sports, namely Gymnastics, Athletics, Swimming and Football Keywords: Intellectual Disability, Fuzzy Inference System, Method Sugeno